SIMULATION OF PROPERTIES OF DUSTY PLASMA ARGON-HELIUM DISHARGE - Kodanova, S. K.; Ramazanov, T. S.; Bastikova, N. H.; Fedoseev, A. V.; Sukhinin, G. I. (Recent Contributions to Physics, 2009)
The numerical results of calculation of the Boltzmann equation in the two member approach, which takes into account elastic and not elastic collisions of electrons in argon and helium mixture, are presented. On the basis of electron energy distribution function of energy the temperature of electrons and potential as a function of concentration of argon atom were derived.